Adaptability: the soft skill that opens doors abroad - Othman, Farrah; Md Kamdari, Nor'azurah; Mohd Sharip, Sharfizie; Abdul Karim, Yaasmin Farzana (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
Working abroad can be a highly rewarding experience that allows individuals to gain new perspectives, interact with different cultures, and grow professionally and personally. However, beyond technical skills and qualifications, adaptability is the key factor for success in a foreign environment. Adaptability helps individuals adjust to cultural differences, overcome unexpected challenges, and remain resilient in unfamiliar situations. By being flexible, open-minded, and proactive, people can handle uncertainty confidently and turn challenges into opportunities.